Cover Feature: Ru‐Catalyzed Transfer Hydrogenation of Nitriles, Aromatics, Olefins, Alkynes and Esters (ChemCatChem 21/2018). Issue 21 (11th November 2018) - Alshakova, Iryna D.; Gabidullin, Bulat; Nikonov, Georgii I.
Abstract : The Cover Feature shows Captain Ruthenium shipping the hydrogen treasure from the Island of Alcohols to the Island of Substrates. In their Full Paper, I. D. Alshakova, B. Gabidullin and G. I. Nikonov report new ruthenium pyrazole‐phosphine complexes as catalysts for transfer hydrogenation of nitriles, heterocycles, olefins, alkynes, and activated esters. Application of these complexes to the reduction of internal alkynes with bulky substituents resulted in selective hydrogenation to olefins with the uncommon E ‐selectivity. More information can be found in the Full Paper by I. D. Alshakova et al on page 4874 in Issue 21, 2018 (DOI: 10.1002/cctc.201801039 ).